Penilaian Properti Psikometrik Instrumen Kualitas Hidup (HRQol) pada Populasi Umum: Tinjauan Sistematik - Restu Nur Hasanah Haris; Rahmat Makmur; Tri Murti Andayani; Susi Ari Kristina (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Quality of life (HRQoL) is a measure of a person's health in physical, spiritual, and emotional, and role functions in the society. Measurement of quality of life (HRQoL) is an important thing to understand and evaluate. Measurements are carried out not only on patients but also on the general population with the use of specific or generic instruments. The instrument used requires a psychometric properties test to ensure its validity and reliability. This article aims to conduct a systematic review of the psychometric properties of quality of life (HRQoL) instruments in the general population. Articles were collected in December 1st to 5th, 2018, from Pubmed and Google Scholar. The assessment was carried out using the checklist properties according to the cohen criteria and included the content validity, construct validity, internal consistency reliability, test-retest, ceiling effect and the level of credibility of the instruments. Among 80 articles obtained there were 24 articles that fulfilled the inclusion criteria. Short Form-36 (SF-36) instrument is the most widely used instrument in measuring the quality of life in the general population (26.6%). Some instruments have not been tested according to the criteria, while almost all instruments show a good level of validation of construct validity using convergent and discriminat validity with cronbach alpha values > 0.7. Test-retest reliability provides a good correlation. Some instruments show a ceiling effect. According to the assessment, the SF-36, SF-6D, EQ-5D, SF-12 and PedsQoL instruments are considered as established instruments. Further validation testing is needed to provide and support the measurement of subsequent quality of life (HRQoL) instruments.